The Influence of Perceived Ease of Use on Behavioral Intention Through Perceived Usefulness as an Intervening Medium in Digital Payment DANA - Hasmiana, Hasmiana; Syamsuddin, Fajar Rakasiwi (Jurnal Economic Resource, 2024)
The purpose of this study is to examine how behavioral intention to use the digital payment service DANA is influenced by perceived ease of use and how perceived usefulness functions as an intervening medium in this connection. The issue addressed is the poor acceptance rate of digital payment services, despite their excellent usability. A population survey of DANA users in Makassar is the methodology employed. Purposive sampling is the method utilized, and 150 respondents who have used DANA for at least six months were included in the sample. A questionnaire addressing the factors of perceived ease of use, perceived usefulness, and behavioral intention was used to gather data. The results of the linear regression analysis show that perceived ease of use has a positive and significant effect on perceived usefulness, which in turn positively affects behavioral intention. These results imply that improving the DANA application's usability can raise users' opinions of its value and, in turn, their desire to keep using the service. In order to design better user-friendly features and promote wider adoption, app developers can benefit greatly from the insights this research offers.